Rationale and design of the CONFIRM‐HF study: a double‐blind, randomized, placebo‐controlled study to assess the effects of intravenous ferric carboxymaltose on functional capacity in patients with chronic heart failure and iron deficiency. (August 2014) - Ponikowski, Piotr; van Veldhuisen, Dirk J.; Comin‐Colet, Josep; Ertl, Georg; Komajda, Michel; Mareev, Viacheslav; McDonagh, Theresa A.; Parkhomenko, Alexander; Tavazzi, Luigi; Levesque, Victoria; Mori, Claudio; Roubert, Bernard; et al.
<x xml:space="preserve">Abstract</x> Background Iron deficiency (ID) is a common co‐morbidity associated with chronic heart failure (CHF), which has unfavourable clinical and prognostic consequences. In Ferinject Assessment in Patients with IRon Deficiency and Chronic Heart Failure (FAIR‐HF), the treatment with i.v. ferric carboxymaltose (FCM) improved symptoms and quality of life over a 24 week period. Ferric CarboxymaltOse evaluatioN on perFormance in patients with IRon deficiency in coMbination with chronic Heart Failure (CONFIRM‐HF) was designed to test a simplifieddosage scheme of FCM during a longer follow‐up period. Methods CONFIRM‐HF, a double‐blind, multi‐centre, prospective, randomized, two‐arm study, enrolled ambulatory patients with symptomatic CHF [New York Heart Association (NYHA) class II/III] with left ventricular ejection fraction ≤45%, BNP >100 pg/mL, or NT‐proBNP >400 pg/mL, presence of ID [defined as ferritin <100 ng/mL, or ferritin 100–300 ng/mL if transferrin saturation (TSAT) <20%], and haemoglobin (Hb) <15 g/dL. Patients were randomized 1:1 to treatment with FCM or placebo for 52 weeks. Primary endpoint is change in 6‐minute walk test (6MWT) distance from baseline to Week 24. Secondary endpoints are: change in 6MWT from baseline to Weeks 6, 12, 36, and 52; Patient Global Assessment score at Weeks 6, 12, 24, 36, and 52; and change from baseline to Weeks 6, 12, 24, 36, and 52 in NYHA class, fatigue score, and quality of life. Safety endpoints include overall safety over the treatment period of 52 weeks. Study medication was administered in single doses as undiluted bolus injection of up to 1000 mg of iron or normal saline at Day 0 and Week 6 up to iron repletion. Further doses of study medication could be administered at Weeks 12, 24, and 36 if a patient still had ID. Results Overall, 304 patients were recruited in 41 centres in nine countries. Conclusion This study will provide further information on the efficacy and safety of iron therapy with i.v. FCM in CHF patients with ID over a 1 year period using a simplified dosing scheme.